Numerical modelling of surface aeration and N2O emission in biological water resource recovery - Qiu, Yuge; Ekström, Sara; Valverde-Pérez, Borja; Smets, Barth F.; Climent, Javier; Domingo-Félez, Carlos; Cuenca, Raúl Martínez; Plósz, Benedek G. (Water research (Oxford), 2024)
•Measurement and modelling of gas mass transfer in oxidation ditch AS reactors.•Identification and calibration of 1- & 2-phase CFD models for surface aeration.•CFD simulation model validation using full-scale DO & N2O liquid sensor data.•Sensitivity ranking of parameters, influencing KLaO2,clean and N2O emission.•Meta-models for KLaO2,clean & N2O emission in hybrid distributed models inferred. Biokinetic modelling of N2O production and emission has been extensively studied in the past fifteen years. In contrast, the physical-chemical hydrodynamics of activated sludge reactor design and operation, and their impact on N2O emission, is less well understood. This study addresses knowledge gaps related to the systematic identification and calibration of computational fluid dynamic (CFD) simulation models. Additionally, factors influencing reliable prediction of aeration and N2O emission in surface aerated oxidation ditch-type reactor types are evaluated. The calibrated model accurately predicts liquid sensor measurements obtained in the Lynetten Water Resource Recovery Facility (WRRF), Denmark. Results highlight the equal importance of design and operational boundary conditions, alongside biokinetic parameters, in predicting N2O emission. Insights into the limitations of calibrating gas mass-transfer processes in two-phase CFD models of surface aeration systems are evaluated. [Display omitted]